Control interno al área de talento humano y su incidencia en la eficiencia eficacia y efectividad de la consultora “asistencia tributaria” de la ciudad de Riobamba período 2018- 2019 - Inca Pontòn, Carina del Rocío (2020)
Nowadays, both public and private companies are exposed to political and socioeconomic changes, which is why they need to incorporate modern technologies and modify their processes, ways of working and organizational culture to maintain their levels of productivity and competitiveness. The purpose of this research is to evaluate the incidence of Internal Control in the efficiency, effectiveness and effectiveness of the talent area, the Tax Assistance consultancy of the city of Riobamba period 2018-2019, and it will be executed through the use of technical aspects that support the investigation. Efficiency is the relationship between the resources used and the achievements achieved; while effectiveness is the ability to achieve the objectives and goals established; effectiveness then could be said to be a combination of efficiency with effectiveness that can be defined as the quantification of the achievement of goals. Weak internal control over the activities of the area means that the proposed objectives are not carried out due to the lack of a system that helps planning and evaluating controls to mitigate risks. The different research methods, techniques and instruments will be used to detect the problems the company is going through. Internal control questionnaires will be carried out on the selected sample, as well as a review of documents and data. Keywords: Internal control, Processes, Human talent, productivity, competitiveness, efficiency, effectiveness, effectiveness, objectives, planning.